The Effect of Trust Supplier on Firm Performance through Information Sharing and Collaboration in Manufacturing Companies - Eric Oktavianus Setiawan; Zeplin Jiwa Husada Tarigan (Petra International Journal of Business Studies, 2022)
Information technology enables companies to build good communication and coordination with external partners. The information system owned by the company can provide fast information for management in determining the company's direction. This research proposed a model to investigate the effect of trust suppliers on firm performance through the mediation of information sharing and collaboration. For this purpose, this study postulates nine hypotheses to be examined. Eighty-five (85) manufacturing companies have been surveyed as the sample in this study. Data collection used a questionnaire designed with a five-point Likert scale. Data analysis used smartPLS software to examine the hypotheses. The result indicated that all hypotheses were supported as follows. Trust supplier, information sharing, and collaboration directly affect firm performance. Interestingly, information sharing and collaboration mediate the influence of trust in suppliers on firm performance. These findings provide a managerial implication on how to improve the firm performance by establishing trust in the supplier, sharing information, and developing collaboration between partners. This study also contributes to the current research in supply chain management.